Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1007/bf01207736
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the age of the recipients on pregnancy rates following donor-oocyte replacement

Abstract: The endometrial factor may be manifested by failure to generate a critical endometrial thickness of 10 mm by sonography in 61% of the older group, compared to only 29% of the younger group. Future studies should address methods of improving the endometrial thickness in the older group, to determine if improved pregnancy rates will occur and to evaluate whether increasing luteal support with extra progesterone may also improve pregnancy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Decreased successful pregnancy outcomes in advanced age are suggested to be caused by decreased blood flow to the endometrium, thus limiting the access to various hormones (10). Similarly, different studies showed that the age of recipients over 45 years negatively affects pregnancy outcomes (11)(12)(13). Contrary to these studies, many stated that the age of recipients in OD does not affect pregnancy outcomes, which is similar to this study (5,(14)(15)(16)(17).…”
Section: Discussionsupporting
confidence: 77%
“…Decreased successful pregnancy outcomes in advanced age are suggested to be caused by decreased blood flow to the endometrium, thus limiting the access to various hormones (10). Similarly, different studies showed that the age of recipients over 45 years negatively affects pregnancy outcomes (11)(12)(13). Contrary to these studies, many stated that the age of recipients in OD does not affect pregnancy outcomes, which is similar to this study (5,(14)(15)(16)(17).…”
Section: Discussionsupporting
confidence: 77%
“…Although there was no significant association between endometrial thickness and implantation, pregnancy outcome was improved in patients showing an endometrial lining thickness >8 mm. There have been controversial reports in this regard (31)(32)(33)(34)(35). We were unable to find a correlation between the ultrasonographic appearance of the endometrium (pattern) and pregnancy or implantation rates (32,35).…”
Section: Discussionmentioning
confidence: 72%
“…Although the effect of increased maternal age on reproduction has been widely studied, the influence of the oocyte donor's age on the recipient's pregnancy success is still controversial. While many investigators have reported that recipient age is inversely related to oocyte donation success (Levran et al, 1991;Check et al, 1993;Meldrum, 1993;Borini et al, 1996;Marcus et al, 2016), others have not observed this relationship (Abdalla et al, 1997;Paulson et al, 1997;Remohi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%